Proposta didática sobre a interação solo-planta e a dinâmica dos ecossistemas amazônicos - Soares, Anderson Colares (2021)
The Soil-Plant Interaction represents for the ecosystem intense dynamics between essential elements that reflect in the functioning and maintenance of the environment. The lack of knowledge about the physiology of plants and soil interferes with the understanding of environmental balance. Therefore, this research aims to provide a teaching proposal on Soil-Plant Interaction giving its relevance to the functioning and maintenance of Amazonian Ecosystems. The guiding research of this study was of a qualitative nature and the means of investigation adopted was action research. The subjects of the research were the students of the 6th year of Elementary School II of the State School Cônego Bento José de Souza, located in the Municipality of Borba-Am, since the curriculum matrixpresents contents related to the research proposal. It was also possible for elementary school II teachers to participate in the construction of the appropriate didactic proposal for the classroom. We emphasize that due to the pandemic of the new coronavirus, this research underwent adaptations, with the activities developed in the following stages: initially the submission to the Brazil platform and with the approval of the proposal, the methodological steps were started. The first stage consisted of a visit to the school to investigate the school's infrastructure, course guiding documents and the research subjects. Important documents identified were the School's Textbook and Pedagogical Political Project. The second stage was the analysis of the curricular components, Textbook and Pedagogical Political Project - PPP. In the third, the diagnosis of the students' previous knowledge was carried out, through a questionnaire applied by Google Forms. On Wednesday, a Pedagogical Workshop via Google Meet took place with Science teachers (Borba and Manaus), entitled “Teaching Practices: Soil-Plant Interaction in Amazonian Ecosystems, seeking to identify the reality of theory and practice disseminated in the classroom and direct the construction of the educational product. The fifth stage consisted of the construction of the educational product and submitted to a commission composed of two PhD professors in the area (botany and soil) and active in the degree courses in order to verify greater contributions beyond those listed in the second stage together with the Education teachers. Basic. Therefore, in the sixth stage, the socialization of the educational product at school was carried out in person in Borba, being carried out through practical and theoretical classes contained in the educational product, contemplating the insertion of the practice in the educational process of the proposal. Thus, the approach of the Soil-Plant Interaction theme in this work identified that there is a great need to value the Amazonian spaces and their biotic and abiotic composition, the results obtained allow us to conclude that the interaction must be addressed in Science Teaching by integrating regional knowledge, it is noted that all the stages were of great importance and contributed to the teaching of Amazonianstudents.